PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA BANK PEMBANGUNAN DAERAH DI INDONESIA DENGAN PERTUMBUHAN KREDIT SEBAGAI VARIABEL INTERVENING (Studi Pada Bank-Bank Pembangunan Daerah Di Sumatera) - Wijaya, Errin Yani (Jurnal Tepak Manajemen Bisnis, 2014)
This study aimed to analyze the effect of financial ratios of banks consisting of CAR, NPL, NIM, ROA and LDR oncredit growth and profit growth in the 8 (eight) Regional Development Bank in Indonesia, especially on theisland of Sumatra in the period 2007-2011. The samples used were taken using census method is to include theentire population there to be sampled to be used in this study.Partial test results indicate that CAR is negative and significant effect on credit growth as well as a significantlypositive effect on earnings growth. NPL ratio partially no significant effect on credit growth but significant effecton earnings growth. ROA ratio is negative and significant effect on credit growth but not significant in affectingearnings growth. NIM ratio is negative and significant effect on the growth of credit, but does not significantlyaffect the growth in earnings. LDR no significant effect on credit growth but significantly and positively affectprofit growth while existing credit growth is able to mediate the perpetually perfect (perfect mediation) betweenfinancial ratios consisting of CAR, NPL, NIM, ROA and LDR on regional development bank profit growth inSumatra in the period 2007 to 2011.Keywords: Financial Ratios, Credit Growth and Profit Growth